Amplified spontaneous emission of perovskite in water: Towards under-water lasing. (May 2022) - Zhang, Yiwei; Zhang, Baohuan; Fu, Yulan; Dou, Fei; Guo, Jinxin; Zhang, Xinping
Abstract: The application of halide perovskite materials as lasing devices has recently attracted great attention. However, the instability of such materials against moisture significantly restrict the application in many occasions. In order to protect the unstable perovskite materials against oxygen and moisture, various encapsulation strategies have been proposed. Regrettably, few of them are designed for aqueous environments. Herein, we demonstrate a photo-polymerized acrylic acid (ADCP) acting as substrate and encapsulation layer to fabricate (CH3 NH3 )PbBr3 (MAPbBr3 ) films and realize amplified spontaneous emission (ASE) with low threshold in water. Lasing threshold from MAPbBr3 films sandwiched by ADCP decreases slightly from 12 μJ/cm 2 in air to ∼9 μJ/cm 2 in water. The specific morphology, superb wettability and high-water stability are expected to contribute to the low ASE threshold. The aqueous environment with higher refractive index is speculated to be one of the origins of the slightly lower ASE threshold. Our results demonstrate a strong potential for applications of perovskite materials in lasing devices in aqueous environment and a new path to realize low threshold lasing. Graphical abstract: Image 1 Highlights: High quality MAPbBr3 films sandwiched by photopolymerized acrylic acid is fabricated. Amplified spontaneous emission (ASE) from perovskite is realized under water. Low ASE threshold and good stability is achived under water. Exciton dynamics of MAPbBr3 films under water are illustrated.